2020
DOI: 10.21873/anticanres.14175
|View full text |Cite
|
Sign up to set email alerts
|

Relative Change in S100 as a Biomarker of Survival in Patients With Metastatic Melanoma Treated With Pembrolizumab

Abstract: Background/Aim: There is a lack of quality biomarkers of survival for patients with metastatic melanoma treated with immunotherapy. Although the baseline level of S100 has prognostic value, its role during/after therapy in survival is unclear. Patients and Methods: We evaluated patients with metastatic melanoma treated with pembrolizumab with the goal of analysing the relationship between a relative change in S100 level at 12 weeks of immunotherapy and survival. Results: Patients with a relative change in S100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The S100 protein, transcribed from a gene on chromosome 21, belongs to the Ca-binding protein family. Studies have indicated a significant increase in the expression of the S100 protein family in tumour tissues, suggesting its potential as a molecular marker for tumour diagnosis [36][37][38][39][40]. Due to the lack of specific clinical markers for diagnosing ICIrelated myocarditis, further investigation into the function of circulating S100A protein levels for predicting irAEs is clinically valuable.…”
Section: Discussionmentioning
confidence: 99%
“…The S100 protein, transcribed from a gene on chromosome 21, belongs to the Ca-binding protein family. Studies have indicated a significant increase in the expression of the S100 protein family in tumour tissues, suggesting its potential as a molecular marker for tumour diagnosis [36][37][38][39][40]. Due to the lack of specific clinical markers for diagnosing ICIrelated myocarditis, further investigation into the function of circulating S100A protein levels for predicting irAEs is clinically valuable.…”
Section: Discussionmentioning
confidence: 99%
“…However, alleged inadequate assessment of individual tumor prognosis by clinicopathological variables led to the need for molecular biomarkers that provide sufficient predictive value to allow personal treatment in the case of cancer. Molecular biomarkers such as S100 levels in pembrolizumab treated patients with metastatic melanoma [ 63 ], higher levels of serum tryptase levels in deeper melanomas and melanomas with ulceration [ 64 ], serum levels of vitamin D in regards to shield site melanoma vs non-shield site melanoma [ 65 ] are examples of a few recent studies. Another widely emerging class is GEP based biomarkers and combinations of these biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Er wird als vielversprechender Parameter in der Diagnostik der hypoxisch-ischämischen Enzephalopathie gehandelt [24]. Bislang wird S-100B außerdem im Rahmen von Immuntherapien bei Melanompatienten als prognostischer Marker genutzt [26].…”
Section: Protein S-100bunclassified